El discurso del vilicus (Petr. Sat. 116, 4-9) y su relación con Horacio (Serm. II, 5) - Carmignani, Marcos Flavio (2013)
This paper analyzes the speech of the vilicus (Sat. 116, 4-9) from its intertextual relations. The main frame of this passage is provided by Odysseus and Hermes meeting in Od. X, 274-309, but this hypotext, in turn, undergoes a parodic transformation by means of the inclusion of a satirical motif (the heredipetae) taken from Horace, Serm. II, 5. We intend to demonstrate that the hypotext from Horaces satire is taken up by Petronius, in words of the vilicus, with the clear intent of introducing a satiric topos that Horace had already used, in order to degrade the Homeric hypotext by means of parodying Odysseus and Hermes meeting and taking the inversion of Tiresias role as a model.